A comprehensive review of spermidine: Safety, health effects, absorption and metabolism, food materials evaluation, physical and chemical processing, and bioprocessing. Issue 3 (27th April 2022) - Zou, Dian; Zhao, Ziyue; Li, Lu; Min, Yu; Zhang, Daiyuan; Ji, Anying; Jiang, Cong; Wei, Xuetuan; Wu, Xian
Abstract: Spermidine, a natural autophagy inducer, has a variety of health effects, such as antitumor, antiaging, anti‐inflammation, cardiovascular protection, and neuromodulation. It has been a hot topic in the field of food processing, and current research findings suggest that spermidine‐rich foods may be used in intervention and prevention of age‐related diseases. In this article, recent findings on the safety, health effects, absorption and metabolism of spermidine were reviewed, and advances in food processing, including the raw materials evaluation, physical and chemical processing, and biological processing of spermidine, were highlighted. In particular, the core metabolic pathways, key gene targets, and efficient metabolic engineering strategies involved in the biosynthesis of spermidine and its precursors were discussed. Moreover, limitations and future perspectives of spermidine research were proposed. The purpose of this review is to provide new insights on spermidine from its safety to its food processing, which will advance the commercial production and applications of spermidine‐rich foods and nutraceuticals.